Pengaruh Konsentrasi Pupuk Organik Cair Batang Pisang Terhadap Pertumbuhan Setek Tebu Metode Bud Chip - Yanto Yanto; Nyoman Natih; Ansyori Ansyori; Damsir Damsir (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Pertanian Dharma Wacana, 2021)
In general, banana stem waste is rarely processed into liquid organic fertilizer (LOF) for plants. This study aims to determine the effect of banana stem LOF concentration on the growth of sugarcane cuttings using the Bud Chip method. Five treatments of banana stem LOF concentration were tested in this study, namely 0 ml/l solution (0%), 150 ml/l solution (15%), 300 ml/l solution (30%), 450 ml/l solution (45%), and 600 ml/l solution (60%). The experiment used a randomized block design with 5 replications. The data were analyzed by means of variance and continued with the comparison test of orthogonal and orthogonal polynomials at 5% significance level. The results showed that sugarcane cuttings given banana stem LOF produced better cuttings growth compared to sugarcane cuttings that were not given banana stem LOF, seen in the observation variables of shoot height, number of leaves, root length, shoot wet weight, shoot dry weight, root wet weight, and root dry weight. In the same observation variable, the concentration of banana stem LOF had a quadratic effect in which it initially increased the growth of sugarcane cuttings, until it reached the optimal concentration between 411.78 - 432.55 ml/l, then the growth of sugarcane cuttings decreased as the concentration of banana stem LOF increased.